GAMBARAN MOTIVASI MAHASISWA PROGRAM STUDI KEPERAWATAN UNTUK MELANJUTKAN PENDIDIKAN PROFESI NERS - Zuryati zuryati (NHM PRESS, 2019)
Profession phase is a continuation of theacademic stage program that must be followed by all graduates of nursing undergraduate whopreviously followed the promise of the court.Based on a preliminary study conducted on March27, 2017 against 10 students of the seventhsemester, students are interested in continuing theners program for a nursing degree. The method used in this study wasdescriptive with cross sectional approach. Thevariable was motivation of VIII students tocontinue professional education ners. Totalpopulation was 138 respondents, the samplingused total sampling, the instrument used wasstudent motivation questionnaire semester VIII. The result of this study obtained that 89respondents with the percentage (64.5%) hadstrong motivation. Tthe data analysis showed thatstudents of 8th semester. Motivation to continuethe professional education in STIKes NgudiaHusada Madura were mostly good. Based on the result, it is expected forteaching team to do approach to students byproviding good support and motivation to thestudents to continue the professional educationprogram.